OSMOTIC DEHYDRATION AND STARCH COATING EFFECT ON THE MICROBIOLOGICAL STABILITY OF APPLES - Šuput, Danijela (Journal on Processing and Energy in Agriculture, 2020)
This paper examines the effect of the osmotic dehydration in sugar beet molasses and starch coating on the microbiological stability of apples. Half of the osmotically treated/untreated apples were protected by starch coating, resulting in four sample groups (K, P, OD, OD+P). E. coli, Salmonella spp. and Listeria monocytogenes were not detected in any of the samples. Enterobacteria were present in samples K and P in the first four days with a decreasing trend, and subsequently were not detectable. The total number of bacteria is uniform within each sample group, and the values ​​are significantly higher for the K and P samples. Yeasts and molds are present in samples K and P, while in OD and OD+P samples they were detected only after the fourth day of storage. The results showed that OD was a suitable method for maintaining microbial stability, whereas starch coating did not justify its purpose.
Keywords: apple; osmotic dehydration; molasses; starch coating; microbial profile